LEARNING OUTCOMES FOR LIFELONG LEARNING IN THE CONTEXT OF LATVIAN VOCATIONAL SECONDARY EDUCATION - Kinta, Gunta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Using learning outcomes, which are defined as statements of what a learner knows, understands and is able to do after learning, may support lifelong learning, since the outcome of education rather that input and process are emphasised. In Latvia vocational education is considered to have important role in the context of lifelong learning. Therefore, this study aimed at exploring views of vocational education students concerning the role of lifelong learning knowledge, skills and competences in vocational secondary education. The questionnaire including 19 statements of general learning outcomes was completed by 1817 vocational education students from 25 vocational schools. The results of the study indicate that the respondents appreciate the importance of these learning outcomes, although in case of some statements the respondents do not have clear understanding how these learning outcomes relate to their occupation.